Disitamab vedotin in combination with immune checkpoint inhibitors for locally and locally advanced bladder urothelial carcinoma: a two-center’s real-world study - Wei, Yongbao; Zhang, Ruochen; Yu, Chenbo; Hong, Zhiwei; Lin, Le; Li, Tao; Chen, Jianhui (Frontiers in Pharmacology, 2023)
Objective: Our study aims to assess the effectiveness and safety profile of Disitamab Vedotin (DV, RC48-ADC), an innovative humanized anti-HER2 antibody conjugated with tubulin-disrupting antimitotic drug monomethyl auristatin E (MMAE) via a cleavable peptide linker. This treatment combined immune checkpoint inhibitors as part of the bladder sparing approach for selected patients suffering from locally and locally advanced bladder urothelial carcinoma. Patients and Methods: We conducted a two-center, real-world study involving locally advanced urothelial carcinoma (UC) patients. Patients were classified based on HER2 expression (IHC 3+/2+/1+) or lack of HER2 expression (IHC 0). The primary endpoint was the objective response rate (ORR), assessed by the investigator following the criteria of RECIST V1.1. Secondary endpoints encompassed the pathological complete response rate (pCR), pathological partial response rate (pPR), and pathological stable disease (pSD), along with recurrence-free survival (RFS), the pathological downstaging rate, and the safety profile of the treatment. Results: In this study, nine patients were enrolled, with a median follow-up duration of 12.0 months. The overall confirmed ORR was 88.9%, Five patients achieved a complete response (CR), and three patients achieved a partial response (PR). The radiological complete response (rCR) aligned perfectly with pCR. The median radiological progression-free survival (rPFS) spanned 12.0 months (range from 8.0–17.0 months). One patient diagnosed with disease progression (PD) underwent a radical cystectomy. The pathological stage evolved from T2N0M0 to T3aN2M0, followed by adjuvant chemotherapy with a gemcitabine-cisplatin (GC) combination radiotherapy. At the nine-month follow-up, neither recurrence nor metastasis was observed. The rate and intensity of complications were manageable among these patients, with no evidence of grade 4 and 5 adverse events. Conclusions: The combination of DV and PD-1 demonstrated considerable activity in the objective response rate (ORR) in patients with HER2 IHC 0/1+/2+/3+ muscle-invasive bladder cancer (MIBC), along with the longest reported median radiological progression-free survival (rPFS) to date. With an extended duration of treatment, the safety profile of DV plus PD-1 was also confirmed to be manageable.